Comparative study of pulpal responses to ProRoot MTA, Vitapex, and Metapex in canine teeth - Woojin Kwon; Ik-Hwan Kim; Chung-Min Kang; Byurira Kim; Yooseok Shin; Je Seon Song (Elsevier, 2021)
Background/purpose: ProRoot MTA, Vitapex, and Metapex are widely used for pulp treatment of primary tooth. The aim of this study was to compare the pulpal responses to ProRoot MTA, Vitapex, and Metapex in a canine model of pulpotomy. Materials and methods: Pulpotomy procedure was performed to 34 teeth (21 incisors and 13 premolars) and ProRoot MTA, Vitapex or Metapex was applicated to artificially exposed pulp tissues. After 13 weeks, the teeth were extracted and processed with hematoxylin-eosin staining for histologic evaluation. All specimens were evaluated in several categorys related to calcific barrier, inflammatory responses and the area of calcific barrier formation was measured. Results: Most of the specimens in the ProRoot MTA group developed a calcific barrier at the pulp amputation site and showed a low level of inflammatory response. However, in comparison to ProRoot MTA group, a small amount of calcific barrier formed in Vitapex and Metapex groups. Conclusion: This in vivo study found that Vitapex and Metapex induced similar pulpal responses but showed poor outcomes compared with using ProRoot MTA. Vitapex and Metapex are therefore not good substitutes for ProRoot MTA in direct pulp capping and pulpotomy.